MYC amplifications are common events in childhood osteosarcoma. (9th May 2021) - De Noon, Solange; Ijaz, Jannat; Coorens, Tim HH; Amary, Fernanda; Ye, Hongtao; Strobl, Anna; Lyskjær, Iben; Flanagan, Adrienne M; Behjati, Sam
Abstract: Osteosarcoma, the most common primary malignant tumour of bone, affects both children and adults. No fundamental biological differences between paediatric and adult osteosarcoma are known. Here, we apply multi‐region whole‐genome sequencing to an index case of a 4‐year‐old child whose aggressive tumour harboured high‐level, focal amplifications of MYC and CCNE1 connected by translocations. We reanalysed copy number readouts of 258 cases of high‐grade osteosarcoma from three different cohorts and identified a significant enrichment of focal MYC, but not CCNE1, amplifications in children. Furthermore, we identified four additional cases of MYC and CCNE1 coamplification, highlighting a rare driver event which warrants further investigation. Our findings indicate that amplification of the MYC oncogene is a major driver of childhood osteosarcoma, while CCNE1 appears recurrently amplified independent of age.